Contribuição ao estudo dos gêneros Lasiodera Gray, 1832 e Philyra Laporte, 1836 (Coleoptera, Cleridae) - Racca Filho, Francisco (1992)
The present work consists of a revision of the species considered up to now in the genus lasiodera Gray, 1832 (Coleoptera, Cleridae) with a detailed study of external morphology as well as males external genitalia which made us to propose the separation into two genera, lasiodera Gray, 1832 and Philyra Laporte, 1836, beeing the second one revalidated. Lasiodera orrata (Klug, 1842) and L. voluptuosa (Thomson, 1860) had not their external genitalia examinated because they are not represented in the colections studied. Descriptions of the genera, species and male genital structures, including measurements of the series and also general considerations are provided. The male genital structures of Philyra helopioides Laporte, 1836 are not represented because only one female specimen of this species is represented in colections studied. The genital structures, showing specific ences, are ilustrated and discussed. To identify the species of the genera, differsystematic keys are presented, based on the external morphological characters. The specific name of Lasiodera malleri (Pie, 1933) is considered to be a synonym of L. ruficollis (Gorham, 1877).